PENGARUH INOVASI DAN ORIENTASI PELANGGAN TERHADAP KINERJA PEMASARAN MELALUI KEUNGGULANBERSAING (STUDI PADA UKM BATIK DI KOTA SEMARANG) - Nusandini, Anisha; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2020)
Marketing performance is a benchmark to determine the extent of the success of Batik SMEs in Semarang in facing intense competition. This study aimed to determine how the effect of innovation and customer orientation on marketing performance through the competitive advantage of Batik SMEs in Semarang. The type of research was explanatory research type with a total sample of 61 respondents used census sampling techniques. The data are collected through questionnaires used Likert measurement scale. The data were analyzed used SPSS 21.0 for Windows. The results showed there is the effect of innovation on competitive advantage with t count value of (9,288)> t table (2,001), there is the effect of customer orientation on competitive advantage with t count value of (9,729)> t table (2,001), there is the effect of innovation and customer orientation to competitive advantage with the F count value of (69.110)> F table (3.156), there is the effect of innovation on marketing performance with a calculated value (7.979)> t table (2.001), there is the effect of customer orientation on marketing performance with t count value of (9.025) )> t table (2,001), there is the effect of competitive advantage on marketing performance with t count value of (9,091)> t table (2,001), there is the effect of innovation on marketing performance through competitive advantage with t count value of (4,079)> t table (2,001) ), there is the effect of customer orientation on marketing performance through competitive advantage with t count value of (3,461)> t table (2,001). Suggestions in this research are Batik SMEs in Semarang to be able to innovate, understand and meet the needs and desires of customers to be excellently competitive so as to improve marketing performance.